A cost-efficient low-weight autonomous profiler for measurements in polar coastal waters and other regions with strong density gradients. (October 2021) - Sandby, Lucas M.; Mejdahl, Jens E.B.; Bjerregaard, Simon H.; Melvad, Claus; Rysgaard, Søren
Graphical abstract: Abstract: The rapid warming of our planet has resulted in accelerated melting of ice in polar regions. Currently we have limited knowledge on how, where and when the surface meltwater layer is mixed with the underlying ocean due to lack of observations in these remote areas. We present a lightweight (17 kg) and low-cost (6000€) instrument for autonomous profiling across the strongly stratified upper layer in Arctic coastal waters, freshened by the riverine input and meltwater from glaciers, icebergs, and sea ice. The profiler uses a specially designed plunger buoyancy engine to displace up to 700 cm 3 of water and allows for autonomous dives to 200 m depth. It can carry different sensor packages and convey its location by satellite communication. Two modes are available: (a) a free-floating mode and (b) a moored mode, where the instrument is anchored to the seafloor. In both modes, the profiler controls its velocity of 12 ± 0.3 cm/s resulting in 510 ± 22 data points per 100 m depth. Equipped with several sensors, e.g. conductivity, temperature, oxygen, and pressure, the autonomous profiler was successfully tested in a remote Northeast Greenlandic fjord. Data has been compared to traditional CTD instrument casts performed nearby.